Pedagogical conditions for the formation of professional competence of students in the direction of training "the art of folk singing" - Augusta V. Uliandina (Publishing house "Sreda", 2023)
The purpose of the article is to analyze the existing approaches to the professional training of folk singers, to identify the necessary approaches for concretizing professional competencies, taking into account the specifics of professional activity and the national and regional specifics of the folklore material of the Volga region, in particular the Chuvash cultural tradition. The material for the study includes normative documents, theoretical works of leading scientists, methodological works of practicing teachers and personal experience of performing and teaching. Based on the method of theoretical analysis, the definition of professional competencies is given as the ability and willingness of students to apply knowledge, skills, experience and personal qualities in accordance with the professional and creative activity in the folk performing arts. It was revealed that the main goal of the implemented approaches in the professional training process is aimed at developing competencies for working with folk song material, vocal and stage work, pedagogical and scientific work. The use of the ethno-cultural approach in the training of folk singers is one of the main ones, the implementation of which allows supplementing the educational standard by determining the content of professional training, taking into account the regional specifics of folklore material, the local folk song tradition, and the characteristic features of the national manner of performance.